Memorandum book of Joseph Smith. - Smith, Joseph, army officer
Memorandum book kept by Smith while serving with the 5th Connecticut Regiment, Continental Army, in 1775. Also contains information added by his descendants in 1838 on the Smith family.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collction.
Keywords: Smith family; United States. -- Continental Army. -- Connecticut Regiment, 5th (1775); Connecticut -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783.; Army officers